Poverty Prevention Need in the North Coast of Central Java Province - Sofianto, Arif (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The coastal communities is one of the main groups of the poorest. The policies that have been implemented in coastal areas often result in some circumstances as ecological destruction, poverty gap and traditional fishing, as well as public dependence on financiers. This research aims to understand the need to reduce poverty in coastal areas according to the characteristics and needs of the community. This type of research is qualitative-descriptive. The location of research in Juwana sub district, Pati Regency, and the Ulujami Subdistrict in Pemalang Regency. Respondents are 100 people, consisting of representatives from local government, community organizations, cooperatives, fishermen, farmers, fishpond farmers, and fish processors. The technique of collecting data using interviews, focus group discussions and observation. Data were analyzed using a model developed by Spradley, which is the unity of a linear process that starts from domain analysis, taxonomic, componential and of cultural themes. The conclusion of this study is that a model of addressing poverty in the north coast of Central Java community is a concept that promotes empowerment principle, commitment to the beliefs, values, customs, common interests, including create transparency, honesty, solidarity and community involvement.